Efficacy of chemo-radiotherapy versus radiotherapy alone in the treatment of esophageal carcinoma - Kumar K.N., Pradeep; L., Ashwini; Yadav, Indira; Tyagi, Anuj; K. C., Lakshmaiah (International Journal of Medical Research and Review, 2019)
Background: The treatment of esophageal carcinoma may demand multiple approaches including combination of radiotherapy and chemotherapy, particularly cases which are considered unresectable, such as upper third esophageal cancers, locally advanced middle and lower third cancers. Methods: This was a prospective, randomized, open-label, single-center study conducted between December 2014 and July 2016. Patients of either sex aged more than 18 years with the confirmed diagnosis of previously untreated advanced esophageal carcinoma were included in the study. Eligible patients were randomized to receive one of the treatments (chemo-radiotherapy [cisplatin] or radiotherapy alone). Response criteria included dysphasia free survival (DySF), disease free survival (DFS), and overall survival (OS). Tolerability was also assessed. Results: A total of 31 patients (chemo-radiotherapy, n=13; radiotherapy alone, n=18) were enrolled in this study. At one year, the probability of remaining dysphagia free was 40% and 20%, respectively for chemo-radiotherapy and radiotherapy alone groups; and the probability of OS was 64% versus 21%, respectively. The median DFS was 12 months and 5 months for chemo-radiotherapy and radiotherapy alone group, respectively. There were no significant differences in both the groups in EBRT, total treatment duration and duration of EBRT. No patient reported thrombocytopenia or nephrotoxicity. Conclusions: Concurrent chemo-radiotherapy with cisplatin can improve dysphasia and OS in patients with esophageal carcinoma.